2017
DOI: 10.1001/jama.2017.7105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of First-Line Chemotherapy Combined With Cetuximab or Bevacizumab on Overall Survival in Patients With KRAS Wild-Type Advanced or Metastatic Colorectal Cancer

Abstract: IMPORTANCE Combining biologic monoclonal antibodies with chemotherapeutic cytotoxic drugs provides clinical benefit to patients with advanced or metastatic colorectal cancer, but the optimal choice of the initial biologic therapy in previously untreated patients is unknown. OBJECTIVE To determine if the addition of cetuximab vsbevacizumab to the combination of leucovorin, fluorouracil, and oxaliplatin (mFOLFOX6) regimen or the combination of leucovorin, fluorouracil, and irinotecan (FOLFIRI) regimen is super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
604
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 732 publications
(633 citation statements)
references
References 23 publications
21
604
1
7
Order By: Relevance
“…Because the RR in patients with ex-ova metastases in our study was almost equivalent to the RRs reported in recent clinical trials using molecular-targeting agents [1,2], our data also reinforces the fact that ovarian metastases are less responsive to CTx, even when using active molecular targeting agents. Ovarian metastases from other primary sites, such as gastric cancer, are also reported to be less responsive to systemic CTx [13].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Because the RR in patients with ex-ova metastases in our study was almost equivalent to the RRs reported in recent clinical trials using molecular-targeting agents [1,2], our data also reinforces the fact that ovarian metastases are less responsive to CTx, even when using active molecular targeting agents. Ovarian metastases from other primary sites, such as gastric cancer, are also reported to be less responsive to systemic CTx [13].…”
Section: Discussionsupporting
confidence: 87%
“…Treatment strategies for metastatic colorectal cancer (mCRC) have markedly progressed in recent years due to the development of effective combination chemotherapy (CTx) regimens that include cytotoxic drugs (e.g., fluoropyrimidine, oxaliplatin, and irinotecan) and molecular targeting agents (e.g., bevacizumab, cetuximab, and panitumumab) [1][2][3]. Recently, median overall survival (OS) has reached almost 30 months in a clinical trial setting for mCRC.…”
Section: Introductionmentioning
confidence: 99%
“…Initial management of unresectable metastatic crc involves a combination of systemic chemotherapy (fluorouracil-leucovorin with either irinotecan or oxaliplatin) and mAb therapies targeting either vascular endothelial growth factor receptor or egfr. The reported os for advanced crc with those treatments ranges from 24 months to 32 months 75,76 .…”
Section: Evidence Summarymentioning
confidence: 99%
“…The incidence of BRAF V600E MT is 5–10% and the prognosis of patients treated by standard chemotherapy remains extremely poor with median progression‐free survival (PFS) after standard first and second line chemotherapies being around 6 and 3 months, respectively . Current pivotal phase III clinical trials, such as FIRE‐3, CALGB80405 and TRIBE, have demonstrated that the overall survival (OS) in patients with wild‐type (WT) RAS mCRC is over 30.0 months, as compared to an OS of approximately 20.0 months in patients with mCRC whose tumors harbor a RAS MT and 13.4 months in patients with mCRC whose tumors harbor a BRAF V600E MT. Based on current knowledge, to maximize the effect of chemotherapy during the initial treatment, combination treatment with bevacizumab and chemotherapy is the preferred regimen for patients with right‐sided colorectal cancer (RCC) harboring WT RAS or patients with both left‐sided colorectal cancer (LCC) and RCC harboring MT RAS or MT BRAF , and combination treatment with an anti‐EGFR antibody and chemotherapy is considered for patients with LCC and both WT RAS and BRAF .…”
Section: Introductionmentioning
confidence: 99%